2013
DOI: 10.1007/s00417-013-2262-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates to the goniodysgensis among juvenile-onset primary open-angle glaucoma patients

Abstract: While two thirds of JOAG patients present with developmental anomalies of the angle, one third have normal appearing angles. High insertion of the iris is the most common form of gonio dysgenesis observed. Those with angle dysgenesis are more likely to present with severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The goniophotographs were graded by 2 masked observers to ascertain the presence or absence of dysgenesis, as described earlier. 15 The findings were tabulated against the success and failure. Although 11 eyes had some form of angle dysgenesis, the rest appeared normal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goniophotographs were graded by 2 masked observers to ascertain the presence or absence of dysgenesis, as described earlier. 15 The findings were tabulated against the success and failure. Although 11 eyes had some form of angle dysgenesis, the rest appeared normal.…”
Section: Resultsmentioning
confidence: 99%
“…Dysgenesis of the angle is not uncommon in eyes with high-pressure POAG, especially those with juvenile OAG. 15,23 There is no study that has looked into the gonioscopic characteristics of angles that underwent laser trabeculoplasty. In the present study, we goniophotographed the angles of the patients before laser to look for dysgenesis as a determinant of success or failure.…”
Section: Discussionmentioning
confidence: 99%
“…Goniodysgenesis has been described not only in congenital and juvenile glaucomas but also among high-pressure adult-onset glaucomas. [13][14][15][16][17] The spectrum of abnormalities is more severe in PCG than juvenile glaucomas. 12 In a previous study, we tried to relate the goniodysgenesis as evaluated by goniophotography with the clinical manifestation of the disease among 126 JOAG patients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the presence or absence of goniodysgenesis among JOAG patients did not correlate with the age at presentation or the highest untreated IOP. 16 It is known that gonioscopy provides only a superficial representation of the histopathologic anomalies affecting the angle. Tawara and Inomata observed the presence of a thick compact tissue in the TM samples of juvenile glaucoma patients, irrespective of whether they had an apparent goniodysgenesis or not.…”
Section: Discussionmentioning
confidence: 99%
“…1 Keratoconus (KC) is a bilateral noninflammatory ectatic corneal dystrophy, recognized as a multifactorial disease with genetic, biochemical, biomechanical, and environmental components [1]. Juvenile glaucoma (JG), on the other hand, is an uncommon and rather diffusely defined entity, considered by some as an earlier onset subset of primary open angle glaucoma (POAG) with no congenital or developmental anomalies, [2] and by others as a developmental glaucoma [3]. We report here 2 eyes in a patient who presented with a subclinical KC co-existent with JG, both eyes demonstrated remarkable increase in keratoconus parameters following surgical lowering of IOP, with a follow up period up to 5 years.…”
mentioning
confidence: 99%